Physical activity and happiness of college students: chain mediating role of exercise attitude and sleep quality - Li, Kehan; Omar Dev, Roxana Dev; Li, Wenhao (Frontiers Media SA, 2025)
Introduction: This study explores the role of physical activity, exercise attitude, and sleep quality in college students’ happiness, aiming to provide a theoretical basis for improving college students’ mental health. Methods: The study employed a whole group sampling method, utilizing a physical activity level scale, exercise attitude scale, sleep quality scale, and happiness scale. A questionnaire survey was conducted with 1,308 college students from four universities in China. Results: The analysis yielded three key findings: (1) Physical activity significantly improves college students’ happiness, and this improvement can be achieved through direct and indirect effects. (2) Positive exercise attitude plays an important mediating role between physical activity and happiness, and a high level of exercise attitude can enhance happiness. In addition, the effect of physical activity on happiness is most significant through exercise attitude. (3) Although sleep quality did not significantly mediate the relationship between physical activity and happiness alone, it played a positive role in the chain mediation path of “physical activity → exercise attitude → sleep quality → happiness.” Discussion: The discovery of the chain mediation path shows that physical activity not only affects happiness, but also indirectly affects college students’ happiness through the combined effects of psychological and physiological factors.